Efficient clustering on Riemannian manifolds: A kernelised random projection approach. (March 2016) - Zhao, Kun; Alavi, Azadeh; Wiliem, Arnold; Lovell, Brian C.
Abstract: Reformulating computer vision problems over Riemannian manifolds has demonstrated superior performance in various computer vision applications. This is because visual data often forms a special structure lying on a lower dimensional space embedded in a higher dimensional space. However, since these manifolds belong to non-Euclidean topological spaces, exploiting their structures is computationally expensive, especially when one considers the clustering analysis of massive amounts of data. To this end, we propose an efficient framework to address the clustering problem on Riemannian manifolds. This framework implements random projections for manifold points via kernel space, which can preserve the geometric structure of the original space, but is computationally efficient. Here, we introduce three methods that follow our framework. We then validate our framework on several computer vision applications by comparing against popular clustering methods on Riemannian manifolds. Experimental results demonstrate that our framework maintains the performance of the clustering whilst massively reducing computational complexity by over two orders of magnitude in some cases. Abstract : Highlights: We propose a kernelised random projection framework for clustering manifold points. We present three projection methods conforming to our proposed framework. We contrast our proposal to clustering methods on manifolds in various vision tasks. We show the proposal obtain significant speed up whilst maintaining the performance. We analyse the parameters contributing to the speed up.